Navigating Sustainability : A Critical Examination of Prague Airport's CSR Initiatives in the Age of Social Media - Trojan, Martin; Čajka, Radek, 1983-; Procházka, Petr; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
The bachelor thesis analyses Prague Airport's Corporate Social Responsibility (CSR) activities critically, emphasising how they align with broader sustainability goals including community involvement, environmental stewardship, and transparent governance. The effectiveness of digital means of communication, such as social media, podcasts, and the airport's official website, in promoting and boosting the visibility of CSR activities is examined in the paper using a qualitative method. Through the analysis of reports and staff interviews, the research delves into how CSR is aligned with the airport's strategic goals, stakeholder engagement, transparency, and the environmental implications of the aviation industry. To place Prague Airport's initiatives within the greater industrial framework, the thesis also contains a comparison analysis of the airports of Hamburg and Heathrow. This comparison helps to clarify the differences in operational scales and approaches to corporate social responsibility. It also highlights how Prague Airport may improve and strengthen its CSR programmes. The primary conclusions underscore the significance of stakeholder participation, show innovative approaches to environmental management, and demonstrate how Prague Airport's CSR initiatives closely match its goal of becoming carbon neutral by 2050.
Vedoucí práce: Radek Čajka
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses